Solid phase microextraction, sand flies, oviposition pheromones, plaster of Paris and siloxanes—What is in common? - Goulart, Thais Marchi; Tosta, Christiann Davis; Machado, Vicente Estevam [UNESP]; da Rocha Silva, Flávia Benini [UNESP]; de Castro, Camila Feitosa [UNESP]; Ortiz, Dennys Ghenry Samillan; Oliveira, Wanderson Henrique Cruz [UNESP]; Pinto, Mara Cristina [UNESP] (Elsevier, 2017)
Sand flies are natural hosts of various microorganisms. Due to their epidemiological importance, sand fly colonies are kept in laboratories to be studied in terms of their biology and vector/host/parasite interactions. In order to investigate the presence of oviposition pheromones in Nyssomyia neivai, experiments using Solid Phase Microextraction (SPME) were performed. However, siloxanes which is an external class of contamination, present in breeding containers made by plaster used to maintain sand flies in colonies, may be hindered the experiments.
Keywords: Nyssomyia neivai; Oviposition; Plaster of Paris; Sand flies; Siloxanes; SPME